1996
DOI: 10.1128/aac.40.2.503
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of fluoroquinolone-resistant Escherichia coli in fecal flora of cancer patients receiving norfloxacin prophylaxis

Abstract: We studied 122 stool samples collected from 25 patients with hematologic malignancies who received prophylactic norfloxacin. Fecal samples were obtained at admission and twice weekly thereafter during prophylaxis. Fluoroquinolone-resistant Escherichia coli strains were isolated from the feces of 10 (40%) of the patients; two patients had fluoroquinolone-resistant E. coli strains prior to beginning norfloxacin treatment, and in the other eight patients, the strains appeared subsequently. One patient developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 27 publications
2
33
0
2
Order By: Relevance
“…4-6 Prior prophylaxis with penicillin or quinolone was also found to increase bacterial resistance in cancer patients. [1][2][3] Prior exposure to antimicrobials thus significantly increases the risk for development of multiresistant GNB, since 45.1% of cases vs only 24.5% of controls (P Ͻ 0.05) received prophylaxis and 41.2% of cases vs 27.5% of controls (P Ͻ 0.05) received broad-spectrum antibiotics. The most significant association for previous exposure was found for imipenem: 19.6% of cases and only 2% of controls (P Ͻ 0.001) received prior therapy with imipenem, which is also reported to be the strongest inducer of ESBL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4-6 Prior prophylaxis with penicillin or quinolone was also found to increase bacterial resistance in cancer patients. [1][2][3] Prior exposure to antimicrobials thus significantly increases the risk for development of multiresistant GNB, since 45.1% of cases vs only 24.5% of controls (P Ͻ 0.05) received prophylaxis and 41.2% of cases vs 27.5% of controls (P Ͻ 0.05) received broad-spectrum antibiotics. The most significant association for previous exposure was found for imipenem: 19.6% of cases and only 2% of controls (P Ͻ 0.001) received prior therapy with imipenem, which is also reported to be the strongest inducer of ESBL.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] There is serious concern related to the increase of quinolone-resistant Escherichia coli and Stenotrophomonas maltophilia, extended spectrum beta-lactamase (ESBL)-producing Enterobacter spp. and Pseudomonas aeruginosa, and imipenem and amikacin resistance in Acinetobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have indicated that antibiotic prophylaxis with fluoroquinolones may also reduce the overall mortality in neutropenic patients of an intermediate-to high-risk group [10] as well as the incidence of fever and bacteraemia [10,11]. However, there is justified concern about the emergence of resistant organisms [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 96%
“…Until 1990, no infections due to fluoroquinolone-resistant E. coli were reported. After 5 years of clinical use, however, a more than fourfold increase in the incidence of bacteremia caused by quinolone-resistant E. coli was observed in cancer patients by several authors [1][2][3][4].…”
Section: Discussionmentioning
confidence: 97%
“…This has been paralleled by a dramatic increase in the incidence of fluoroquinolone-resistant bacteria. In 1994, the emergence of quinolone-resistant Escherichia coli in neutropenic cancer patients was observed in several institutions in Europe [1][2][3][4]. A correlation between previous administration of quinolones and the development of resistance to these agents was suspected and has been proven by several authors [5,6].…”
Section: Introductionmentioning
confidence: 99%